Regional Regression Correlation Model of Microplastic Water Pollution Control Using Circular Economy Tools - Antohi, Valentin Marian; Ionescu, Romeo Victor; Zlati, Monica Laura; Iticescu, Catalina; Georgescu, Puiu Lucian; Calmuc, Madalina (International journal of environmental research and public health, 2023)
Water pollution caused by microplastics represents an important challenge for the environment and people’s health. The weak international regulations and standards in this domain support increased water pollution with microplastics. The literature is unsuccessful in establishing a common approach regarding this subject. The main objective of this research is to develop a new approach to necessary policies and ways of action to decrease water pollution caused by microplastics. In this context, we quantified the impact of European water pollution caused by microplastics in the circular economy. The main research methods used in the paper are meta-analysis, statistical analysis and an econometric approach. A new econometric model is developed in order to assist the decision makers in increasing efficiency of public policies regarding water pollution elimination. The main result of this study relies on combining, in an integrated way, the Organisation for Economic Co-operation and Development’s (OECD) data on microplastic water pollution and identifying relevant policies to combat this type of pollution.